The Andean Southern Volcanic Zone: a review on the legacy of the latest volcanic eruptions - Romero, Jorge E. (2024)
The Andean Southern Volcanic Zone (SVZ) concentrates many of the most active volcanoes of the Andean continental arc, as well as the region’s most recent and impactful volcanic eruptions. In this contribution, we briefly revise the general characteristics of the SVZ volcanism and provide a synthesis of the scientific findings related to the latest volcanic eruptions (<35 years) in this arc segment. These eruptions alone have inspired >430 peer-reviewed publications with over 9,000 citations, with large-magnitude (VEI 4-5) eruptions being the most studied. Our study shows that SVZ research has been primarily focused on environmental and atmospheric impacts (29%), eruption descriptions and physical volcanology (20%), volcanic hazard and risk assessments (15%), and other investigations complementary to volcanology. Whereas the least silicic eruptions (e.g., Llaima 2008-2009 and Villarrica 2015) shed light on magma replenishment and degassing dynamics controlling eruption styles, intermediate eruptions (andesitic-dacitic) offered clues on either rapid or slow eruption initiation, with relevant findings on phreatic-to-magmatic style transitions and eruption triggering mechanisms. On the other hand, silicic (i.e., rhyolite-rhyodacite) eruptions provided unique observations on rapid magma ascent, high-rate magma extrusion, rheology, fragmentation processes, and style transitions. These recent eruptions have also inspired a new generation of tephrochronological, tephrostratigraphical, and physical volcanology studies, aimed at assessing the long-term (kyr-scale) evolution of the volcanic systems and their associated hazards. We debate how the knowledge gained from research and the long-term human coexistence with volcanoes are relevant to reducing volcanic risk in the SVZ. Finally, we discuss how challenges and opportunities emerging from other disciplines can complement our understanding of volcanism in this active region.